Zarządzanie kapitałem intelektualnym w działalności szkoleniowej - Nawara, Izabela (Selected problems of implementing participation practice in an organization, 2006)
The author focuses on selected issues related to intellectual capital management in training companies. The foremost assumption has been made that knowledge becomes the most important asset and out of knowledge-management companies are training companies which most eagerly and aptly adopt methods and tools facilitating transition from tacit to explicit knowledge. The most important approaches and strategies of intellectual capital management have been described in relation to training companies and, therefore, the implications. Finally, methods of a survey conducted among eight training companies of diversified origin and its results are presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 249-257